Preparation and Characterization of Cu (II), Mn(II) and Zn(II)complexes with new sulfamethoxazole Compounds - Baghdad Science Journal (Baghdad Science Journal, 2017)
Acetophenone sulfamethoxazole and 3-Nitrobenzophenone sulfamethoxazole were prepared from the reaction of sulfamethoxazole with two ketones. The prepared ligands were identified by (C.H.N) analysis and UV-VIS, FT-IR spectroscopic techniques. Metal complexes of the two ligands were prepared in an aqueous alcohol with Zn (II), Mn (II) and Cu (II) ions with a molar ratio1:1. The proposed general formula for the resulting complexes was [ML.CL2.H2O]H2O .The complexes were characterized by (C.H.N) technique , spectroscopic methods ,conductivity, atomic absorption ,magnetic susceptibility measurements and melting point. According to the results obtained, the suggested geometry is to be octahedral for all the complexes.